Leading the way–Understanding women’s university leadership during crisis through a feminist educational leadership lens - Schiffecker, Sarah; McNaughtan, Jon (Frontiers in Education, 2022)
Crisis leadership in higher education has received scholarly attention before COVID-19, yet found itself even more in the focus of global leadership research since 2020. This article employs the theoretical framework of Feminist Educational Leadership (FEL) to better understand the crisis leadership of five women university presidents from three different continents and five different countries during the COVID-19 pandemic. Through content analysis, the researchers identified themes related to the four components of FEL (concerns for social justice and equity for all stakeholders, empowerment of all stakeholders, establishment of a sentiment of caring, and fighting existing injustices) in the presidents’ qualitative interviews for a larger project on university presidential leadership during COVID-19. The findings show that women university presidents employ FEL in order to successfully lead their institutions through crises.